2014
DOI: 10.4049/jimmunol.1400110
|View full text |Cite
|
Sign up to set email alerts
|

Airway Uric Acid Is a Sensor of Inhaled Protease Allergens and Initiates Type 2 Immune Responses in Respiratory Mucosa

Abstract: While type 2 immune responses to environmental antigens are thought to play pivotal roles in asthma and allergic airway diseases, the immunological mechanisms that initiate the responses are largely unknown. Many allergens have biologic activities, including enzymatic activities and abilities to engage innate pattern-recognition receptors such as TLR4. Here we report that IL-33 and thymic stromal lymphopoietin (TSLP) were produced quickly in the lungs of naïve mice exposed to cysteine proteases, such as bromel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 80 publications
4
85
0
6
Order By: Relevance
“…Thus, we took a similar approach to induce NP-Ficoll-specific Ig responses by exposing mice intranasally (i.n.) to NP-Ficoll together with a cysteine protease, bromelain, as an adjuvant (22). We isolated lung ILC2s from non-sensitized WT C57BL/6 mice that had been injected i.p.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we took a similar approach to induce NP-Ficoll-specific Ig responses by exposing mice intranasally (i.n.) to NP-Ficoll together with a cysteine protease, bromelain, as an adjuvant (22). We isolated lung ILC2s from non-sensitized WT C57BL/6 mice that had been injected i.p.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are not restricted to the use of CT since similar preventionreconstitution of this phenotype was observed in a model of skin sensitization where tissue damage was caused by tapestripping. Evidence for the role of UA (18,19), IL-33 (8,20), ATP (21), and HMGB1 (22) in allergic airway inflammation, food allergy, and allergic rhinitis argue for the critical importance of tissue damage and the pervasive role of alarmins in the initiation of allergic sensitization and, ultimately, Th2 immunity. In a model of oral sensitization, such as the one used here, we have shown that IL-33 plays a similarly critical role (8) and, more recently, we have demonstrated that eosinophils and, specifically, eosinophil peroxidase (EPO) are essential for the development of peanut allergy (13).…”
Section: Discussionmentioning
confidence: 98%
“…RAGE is highly expressed on type I alveolar epithelial cells (41–43), while IL-33 localizes to nuclei and is released by type II alveolar epithelial cells in response to damage (4951). How RAGE activation might direct increased IL-33 expression is unclear, but it is known that type I and type II alveolar epithelial cells communicate through multiple paracrine and juxtacrine signaling pathways (5255). Future studies will elucidate how these pathways propagate upstream inputs from RAGE.…”
Section: Discussionmentioning
confidence: 99%